Supermarket deserts in the Polish trade landscape in comparison with the global development trends in this sector - Rochmińska, Agnieszka (European Spatial Research and Policy, 2023)
The article presents the development of food retail in Poland in comparison with global trends, characterised by the tendency to replace small traditional food stores with large-format stores, such as supermarkets and hypermarkets. This tendency has led to the emergence of retail and food deserts in numerous countries. This is a major problem from the perspective of both practitioners and researchers. In Poland, like in many other countries in the world, similar processes in retail development occur, therefore, researchers should pay attention to the emergence of retail deserts, the so-called ‘supermarket deserts,’ as well as some limitations in terms of access to supermarkets. Many territorial units in Poland, especially in eastern Poland, have no large-format stores. These areas constitute retail deserts and require further micro-scale research.